The global crisis and equity market contagion - Geert Bekaert; Michael Ehrmann; Marcel Fratzscher; Arnaud Mehl (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
We analyze the transmission of the financial crisis of 2007 to 2009 to 415 country-industry equity portfolios. We use a factor model to predict crisis returns, defining unexplained increases in factor loadings and residual correlations as indicative of contagion. While we find evidence of contagion from the U.S. and the global financial sector, the effects are small. By contrast, there has been substantial contagion from domestic markets to individual domestic portfolios, with its severity inversely related to the quality of countries' economic fundamentals. This confirms the wake-up call hypothesis, with markets focusing more on country-specific characteristics during the crisis.
Keywords: F3; G14; G15; 330; contagion; financial crisis; equity markets; global transmission; market integration; country risk; factor model; financial policies; FX reserves; current account